Pattern Recognition Approach for Formation Control for Swarm Robotics Using Fuzzy-Kohonen Networks - Siti Nurmaini; Bambang Tutuko; Aditya Aditya (IAES Indonesia Section, 2015)
Recent advances in robotics have started makingit feasible to deploy large numbers of inexpensive robotsfor tasks such as surveillance and search. However,coordination of multiple robots to accomplish such tasksremains a challenging problem. This paper describes newalgorithm Fuzzy-Kohonen Networks (FKN) to achieve realtimereactive formation control for swarm robots.